PERBANDINGAN NILAI DIAGNOSTIK IGE SPESIFIK TUNGAU DEBU RUMAH, METODE ELISA DAN IMUNOBLOT PADA RINITIS ALERGI - Janti Tri Habsari; Aryati Aryati; Dwi Reno Pawarti (Indonesian Association of Clinical Pathologist and Medical laboratory, 2016)
The detection of allergen types is very helpful in allergic rhinitis (AR) management. Some methods had been performed to examinethe specific IgE due to HDM such as ELISA and immunoblot methods. The aim of this research is to know the difference of specificIgE diagnostic value due to HDM between ELISA and immunoblot in allergic rhinitis method which is expected to be used as in vitroalternative method which is safe, fast, effective, with a high sensitivity and specificity by provement. The samples were allergic rhinitisand non-allergic rhinitis patients at ENT of Head and Neck Out patients Clinic of Dr. Soetomo Hospital Surabaya. The sera was examinedfor specific IgE due to HDM by ELISA and immunoblot methods and then analyzed for its diagnostic value using the 2 x 2 table with a95% confidence interval. The comparation between both methods were analyzed with Wilcoxon test. The diagnostic value of the specificHDM IgE with immunoblot method showed sensitivity of 90% and 80% specificity, positive predictive value 90% and the negative 80%and diagnostic efficiency 86.67%. The positive likelihood ratio 4.5 and the negative one 0.125. The diagnostic value of the specific IgEHDM/D.p with ELISA showed a sensitivity of 75% and specificity 75%, the positive predictive value 85.71% and the negative one 0%and diagnostic efficiency 75%. The positive likelihood ratio was 3 and the negative one 0.33. The diagnostic value of the specific IgEHDM with immunoblot showed a sensitivity of 90% and specificity 80%, the positive predictive value 90% and the negative one 80%and the diagnostic efficiency 86.67%. The positive likelihood ratio was 4.5 and the negative one 0.125. The difference of diagnostic valuein both methods revealed that the p value was 0.013. It can be concluded in this study that there was a significant difference of specificIgE due to HDM between ELISA and immunoblot methods in allergic rhinitis.